PHYTOCHEMICAL INVESTIGATION OF METHANOLIC EXTRACT OF ARTEMISIA VULGARIS, L. LEAVES - A KAMARUL HANIYA; PR PADMA (International Journal of Pharma and Bio Sciences, 2014)
The deleterious effect of oxidative stress can be counteracted by the presence of antioxidants. But due to the adverse side effects caused by synthetic antioxidants, the search for natural antioxidants has become important.In the present study, the methanolic extract of Artemisia vulgaris, L. was screened for the presence of phytochemicals by qualitative preliminary phytochemical screening, HPTLC, HPLC and GC-MS methods. Qualitative screening indicated the presence of phenolics and flavonoids. HPTLC results showed the presence of six phenols and four flavonoids. The HPLC spectrum showed 3 peaks, indicating the presence of three principle components. The GC results showed the presence of five major components at retention times 9.244, 10.174, 11.487, 13.388 and 13.568 respectively. Thus, the phytochemical analyses of methanolic extract of Artemisia vulgaris, L. leaves revealed the presence of phenolics, flavonoids and sesquiterpenoid type compounds.